Catalytic oxidation of volatile organic compounds (VOCs) – A review. (September 2016) - Kamal, Muhammad Shahzad; Razzak, Shaikh A.; Hossain, Mohammad M.
Abstract: Emission of volatile organic compounds (VOCs) is one of the major contributors to air pollution. The main sources of VOCs are petroleum refineries, fuel combustions, chemical industries, decomposition in the biosphere and biomass, pharmaceutical plants, automobile industries, textile manufacturers, solvents processes, cleaning products, printing presses, insulating materials, office supplies, printers etc. The most common VOCs are halogenated compounds, aldehydes, alcohols, ketones, aromatic compounds, and ethers. High concentrations of these VOCs can cause irritations, nausea, dizziness, and headaches. Some VOCs are also carcinogenic for both humans and animals. Therefore, it is crucial to minimize the emission of VOCs. Among the available technologies, the catalytic oxidation of VOCs is the most popular because of its versatility of handling a range of organic emissions under mild operating conditions. Due to that fact, there are numerous research initiatives focused on developing advanced technologies for the catalytic destruction of VOCs. This review discusses recent developments in catalytic systems for the destruction of VOCs. Review also describes various VOCs and their sources of emission, mechanisms of catalytic destruction, the causes of catalyst deactivation, and catalyst regeneration methods. Highlights: Common VOCs, their sources and impacts. Alternative techniques for VOCs destruction/separation. Catalytic oxidation of VOCs. Mechanism of catalytic oxidation of VOCs. Recent development of VOCs oxidation catalysts.